High-temperature oxidation mechanisms of nano-/submicro-scale lamellar structures in an intermetallic alloy. (October 2019) - Wu, G.D.; Cui, G.R.; Qu, S.J.; Feng, A.H.; Cao, G.J.; Ge, B.H.; Xiang, H.P.; Shen, J.; Chen, D.L.
Abstract: The aim of this study was to elucidate the oxidation mechanisms of γ-TiAl/α2 -Ti3 Al lamellar structures in a TiAlNbCr intermetallic alloy at a high temperature. The original γ-TiAl/α2 -Ti3 Al lamellae in the alloy were transformed into H-Ti2 AlN/α2 -Ti3 Al lamellae, and κ-Al2 O3, α-Al2 O3 and some remaining γ-TiAl phases were observed to be co-existent. The first-principles calculations of density-functional type based on the generalized-gradient approximation revealed that the metastable κ-Al2 O3 can be converted into the stable α-Al2 O3 . TiN and Ti2 AlN could be converted into each other to form κ-Al2 O3 under specific conditions. Thus the oxidation path of the intermetallic alloy is established as follows: γ  −  TiAl  → ( H  −  Ti 2 AlN,   TiN ) →  κ  −  Al 2 O 3  →  α  −  Al 2 O 3 . Graphical abstract: Unlabelled Image